Revision ACL reconstruction using quadriceps or hamstring autografts leads to similar results after 4 years: good objective stability but low rate of return to pre-injury sport level - Barié, Alexander; Ehmann, Yannick; Jaber, Ayham; Huber, Jürgen; Streich, Nikolaus (Knee surgery, sports traumatology, arthroscopy, 2019)
PurposeDue to the increased importance of revision ACL reconstruction, this study aims to evaluate the outcome 4 years after the surgery, compare two revision strategies and identify factors that influence the results.MethodsSeventy-nine patients who received a revision ACL reconstruction were retrospectively evaluated. All patients were assessed with an average follow-up of 4.4 years (range 3.3-5.5 years). The results of patients treated with a quadriceps autograft were compared with those treated with a hamstring autograft.ResultsNinety-seven percent of patients had a KT-1000 side-to-side difference of ≤ 5 mm (mean 1.7 ± 2.0 mm). Pivot-shift test was absent or minor in 95%. In the SLTH-test, 70% of patients reached 90% of the contralateral side. The mean Lysholm score on follow-up was 83 ± 12 (56% excellent/good). The mean IKDC 2000 subjective evaluation score was 81 ± 14 (58% normal/almost normal). The median Tegner activity score was 6 (range 3-10), a median of 2 levels worse than before the first injury. Return to sport rate was 89% but only 34% of patients reached their pre-injury sport level. Most common cause for this reduction was fear of another injury. Three patients suffered a re-rupture. Patients with a hamstring autograft performed pivoting sports more often, but had worse pivot-shift results compared to those with a quadriceps autograft. No significant influence was seen for other parameters. Young, male patients with a high activity level and no chondral damage had the best results.ConclusionThrough revision ACL reconstruction, the goal of stabilizing the knee can be achieved in the majority of patients. However, a good function and a high activity level are significantly less common in these patients. The main reason for this is fear of a renewed ACL-injury. Both quadriceps and hamstring autografts were able to achieve a good outcome. Young, male, patients with a normal BMI, a high activity level and without cartilage damage seem to benefit the most from revision ACL surgery. The discrepancy between the good laxity restoration and the lower activity rate should therefore be a main point in clinical counseling when deciding for or against revision ACL-Reconstruction.Level of evidenceIII.